Fragmentation Functions of Light and Heavy Quarks in Vacuum - Selim, Marwa (AUC Knowledge Fountain, 2025)
However, no single quark has been observed in nature since quarks exist in bound states. It is believed that there was a time before the formation of hadronic matter when quarks and gluons were asymptotically free and exhibited a state known as Quark-Gluon Plasma (QGP). Signatures of such a state, like jet quenching and elliptic flow, have been detected in heavy-ion collisions at RHIC and LHC experiments. The purpose of this study is to set a baseline for the QGP studies through the study of the fragmentation functions of light quarks -π 0 as an example- and heavy quarks -D0 and D+ - were chosen. PYTHIA8 was used to simulate proton-proton collisions at RHIC center-of-mass energy √sNN = 200 GeV. Results showed strong suppressions in the near-side yields in the case of D mesons compared to π 0. In PYTHIA, no QGP is formed, then our results would serve as good references for the real data. By comparing the yields of heavy and light quarks in the vacuum, the results displayed differences that should be considered while interpreting the data from real collider experiments. These differences are primarily because charm quarks follow different fragmentation mechanisms than light quarks.